2012
DOI: 10.1620/tjem.227.321
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Colony-Forming Capacity of Circulating Endothelial Progenitor Cells in Patients with Emphysema

Abstract: Chronic obstructive pulmonary disease (COPD) is classified into emphysema and chronic bronchitis, which are thought to result from different pathophysiological pathways. Smoking-induced lung parenchymal destruction and inadequate repair are involved in the pathogenesis of emphysema. In addition, decreased expression of vascular endothelial growth factor and increased endothelial cell apoptosis in the lung may participate in emphysema pathogenesis. As stem cells, circulating endothelial progenitor cells (EPCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Palange et al15 and Fadini et al16 had shown that circulating EPCs decreased in patients with COPD and could be correlated with disease severity. Moreover, Kim et al17 reported that EPCs may be associated with the development of emphysema, and circulating EPCs were an independent predictor of the presence of emphysema. Lam et al26 also revealed that autologous transplantation of EPCs preserves pulmonary endothelial function and maintains the integrity of pulmonary alveolar–capillary barrier by reducing infiltration of leukocytes and decreasing water content, hyaline membrane formation, and hemorrhage in the lung parenchyma of rabbits with acute lung injury and end-stage acute respiratory distress syndrome (ARDS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palange et al15 and Fadini et al16 had shown that circulating EPCs decreased in patients with COPD and could be correlated with disease severity. Moreover, Kim et al17 reported that EPCs may be associated with the development of emphysema, and circulating EPCs were an independent predictor of the presence of emphysema. Lam et al26 also revealed that autologous transplantation of EPCs preserves pulmonary endothelial function and maintains the integrity of pulmonary alveolar–capillary barrier by reducing infiltration of leukocytes and decreasing water content, hyaline membrane formation, and hemorrhage in the lung parenchyma of rabbits with acute lung injury and end-stage acute respiratory distress syndrome (ARDS).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was demonstrated that EPCs were decreased in patients with COPD and correlated with hypoxemia, severity of airway obstruction, and peak oxygen consumption 15,16. Some studies also suggest a possible link between systemic inflammation and a decrease in circulating progenitors 1517. Taken together, we hypothesized that EPCs play an important role in the pathogenesis of COPD, and the possible protective role of increasing EPCs in a smoking-induced COPD model can provide more insight into the treatment of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the EPCs of COPD patients exhibited reduced cluster-forming numbers and impaired cell migratory capacity, suggesting that the capacity of EPCs to repair dysfunctional endothelium is compromised in COPD [51]. These dysfunctional characteristics of COPD EPCs were also confirmed in a study by Kim and colleagues [53], where they observed significantly lower colony-forming units and lower migratory capacity of circulating EPCs isolated from patients with emphysema. These findings from BPD and COPD studies highlight the potential of stem/progenitor cell supplementation for repair/regeneration of the lung.…”
Section: Therapeutic Potential Of Stem/progenitor Cells For Lung Rmentioning
confidence: 80%
“…Alternatively, recruited EPCs to the airways may have increased activity that drives inflammation and enhances EC proliferation in the vascular wall resulting in pulmonary vessel remodelling and PH (6). Conversely, other groups have theorized inadequate or impaired mobilization of EPCs from the BM, thereby preventing repair processes within the pulmonary vasculature (5,7,8).…”
Section: Review Articlementioning
confidence: 99%
“…EPCs have been phenotypically difficult to isolate from HPCs given that they express similar markers including, CD34, CD31, and vascular endothelial growth factor (VEGF) receptor 2 (VEGFR2) (7). Initially, EPCs were defined as cells positive for CD34 and VEGFR2, however these markers are also expressed on mature ECs and were therefore deemed insufficient to identify the population of interest (13,14).…”
Section: Phenotypic Identification Of Epcsmentioning
confidence: 99%